A comparative analysis of the phytochemical composition and in -vitro antioxidant activity of various parts of Psidium guajava Linn found in Sri Lanka - Rajkumar, G.; Jayathilaka, U.S.A.; Vinotha, S. (My University, 2024)
The incidence of disease is growing worldwide, particularly in developing countries. Psidium guajava L. (Myrtaceae) usually recognized as guava, is a good snack for patients due to its low-calorie and high soluble fiber contents. The current study was to assess the antioxidant activity with the phytochemical characteristics of methanolic, ethanolic, and aqueous extracts of various parts of Psidium guajava. After shade drying, each part was ground into a powder and extracted separately with various solvents using cold extraction method. Standard screening methods were followed and the colorimetric method was used to access the total contents of phytochemicals. The findings demonstrated that tannins, glycosides, phenols, and flavonoids were existing in all of the extracts from the various components. The total tannin, phenolic, flavonoid, and alkaloid contents of Psidium guajava’s leaves and bark were higher than those of the plant’s fruits and seeds. Furthermore, when compared to other parts, methanolic leaf extract had the highest DPPH and ABTS antioxidant activity since it had the lowest IC50 values (19.17±0.258 and 356.16±0.156 mg/ml, respectively). Finally, this work offers a thorough examination of the antioxidant and phytochemical characteristics of the Sri Lankan-grown Psidium guajava variety, which the scientific community can utilize for further research.
Keywords: Antioxidant; Different parts; Phytochemical; Psidium guajava; Sri Lanka